Low temperature grown CuBi2O4 with flower morphology and its composite with CuO nanosheets for photoelectrochemical water splitting - Patil, Rupali; Kelkar, Sarika; Naphadeab, Rounak; Ogale, Satishchandra (Journal of Materials Chemistry A, 2014)
In this work we highlight a peculiar synthesis protocol for the p-type ternary metal oxide system of copper bismuth oxide (CuBi2O4), which yields a highly crystalline spherulitic morphology at a low temperature of 78 degrees C. We associate this growth with the hydrogen bonding effects imparted by the ethanol-water co-solvent system used for the synthesis. We present a detailed growth mechanism by evaluating different synthesis conditions systematically. Furthermore we show that upon the use of the non-stoichiometric (excess copper) precursor mixture under the same experimental conditions the growth of spherulitic CuBi2O4 changes the size and type of the spherulites. Interestingly, careful optimization of the nonstoichiometric synthesis presents a complete impediment to the spherulitic growth and produces a composite of nanorods of CuBi2O4 and nanosheets of CuO. This anisotropic nanocomposite shows an order of magnitude higher surface area as compared to spherulitic CuBi2O4. Since both CuBi2O4 and CuO are visible light absorbing p-type semiconductors, when the synthesized nanocomposite materials are examined as photoelectrochemical (PEC) photocathodes for water splitting, they show a remarkable dependence on the morphology and phase constitution. Almost 13-fold stronger PEC response is observed as the morphology changes from spherulites to nanorods.

Water electrolysis with a conducting carbon cloth: subthreshold hydrogen generation and superthreshold carbon quantum dot formation - Biswal, Mandakini; Deshpande, Aparna; Kelkar, Sarika; Ogale, Satishchandra (ChemSusChem, 2014)
A conducting carbon cloth, which has an interesting turbostratic microstructure and functional groups that are distinctly different from other ordered forms of carbon, such as graphite, graphene, and carbon nanotubes, was synthesized by a simple one-step pyrolysis of cellulose fabric. This turbostratic disorder and surface chemical functionalities had interesting consequences for water splitting and hydrogen generation when such a cloth was used as an electrode in the alkaline electrolysis process. Importantly, this work also gives a new twist to carbon-assisted electrolysis. During electrolysis, the active sites in the carbon cloth allow slow oxidation of its surface to transform the surface groups from COH to COOH and so forth at a voltage as low as 0.2V in a two-electrode system, along with platinum as the cathode, instead of 1.23V (plus overpotential), which is required for platinum, steel, or even graphite anodes. The quantity of subthreshold hydrogen evolved was 24mLcm(-2)h(-1) at 1V. Interestingly, at a superthreshold potential (>1.23V+overpotential), another remarkable phenomenon was found. At such voltages, along with the high rate and quantity of hydrogen evolution, rapid exfoliation of the tiny nanoscale (5-7nm) units of carbon quantum dots (CQDs) are found in copious amounts due to an enhanced oxidation rate. These CQDs show bright-blue fluorescence under UV light.
Keywords: Carbon; electrolysis; Hydrogen; photoluminescence; quantum dots